SPRINT INDIA: Regional Variations in Primary and Secondary Stroke Outcomes Based on Baseline Characteristics in North and South Indian Sites - Somasundaram Kumaravelu; Shweta Jain Verma; Rimpi Arora; Deepti Arora; KS Arya Devi; Aneesh Dhasan; Padmavathyamma Narayanapillai Sylaja; Dheeraj Khurana; Pamidimukkala Vijaya; Biman Ray; Vivek Nambiar; Sanjith Aaron; et al. (Annals of Indian Academy of Neurology, 2025)
Background and Objectives: Regional differences in stroke prevalence and outcomes in India, driven by demographic and risk factors, are crucial for guiding effective prevention and management strategies. This subanalysis of Secondary prevention with a structured semi-interactive stroke prevention package in INDIA (SPRINT INDIA) randomized controlled trial compared the demographics, risk factors, and clinical outcomes of stroke patients from North and South India to identify regional differences and inform targeted interventions for stroke prevention. Methods: The study analyzed data of 4298 participants from 31 stroke centers across India, focusing on demographics, stroke types, and risk factors. In this study, Mumbai, located at 19.07°N in western India, serves as the dividing line between North and South India. One-year follow-up data from 3038 patients were utilized to examine regional disparities between North and South India. Results: South Indian stroke patients were predominantly rural (60.1%) and less educated (58.2%), while North Indian patients were mostly urban (64.2%). South Indian patients had higher incidence of ischemic stroke (91.1% vs. 73.5%, P = 0.001) and higher rates of large artery atherosclerosis (33.6% vs. 19.7%, P = 0.001), hypertension, type 2 diabetes, smoking, and alcohol consumption, but better medication adherence. In contrast, North Indian patients had higher high-density lipoprotein, drug use, and tobacco use. At 1-year follow-up, North Indian patients had more high-risk transient ischemic attacks and poorer lifestyle-related outcomes, despite South Indians having higher systolic blood pressure and fasting glucose levels. Conclusion: Region-specific strategies are crucial. Block randomization may help. South India needs better lifestyle modification programs, while North India requires improved health education and medication adherence strategies. Trial registration: CTRI/2017/09/009600